Peningkatan Keterampilan Membaca Intensif Biografi Tokoh dengan Pembelajaran Kooperatif Tipe Jigsaw Siswa Kelas VII SM - Haudiyah Haudiyah (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of this Classroom Action Research is to describe the improvement of biographical intensive reading skills of figures with jigsaw type cooperative learning in class VII. Consists of two cycles and each cycle consists of planning, implementation, observation, evaluation, and reflection. Data collection is done with test techniques, non-tests, observation of teacher activities, observation of student activities, journals, interviews, documentation, and literature. Data are analyzed quantitatively and qualitatively. The results obtained are that the improvement in process is indicated by all indicators of action carried out by all students. While the increase in results can be seen from the average value of individual students, namely: 64.28% in the first cycle to 92.85% in the second cycle, or the average value of each cycle has increased from 71.25 in the first cycle to 80.17 in cycle II. Based on the results of the discussion it can be concluded that the ability of intensive reading of biographies of figures with the jigsaw method for students of class VII has increased, both in terms of process and results.